Gaseous Detector with Sub-keV Threshold to Study Neutrino Scattering at Low Recoil Energies - A. V. Kopylov; I. V. Orekhov; V. V. Petukhov; A. E. Solomatin (Advances in High Energy Physics)
Gaseous detector with a sub-keV electron equivalent threshold is a very perspective tool for the precision measurement of the neutrino magnetic moment and for observing coherent scattering of neutrinos on nuclei. The progress in the development of low noise electronics makes it possible to register the rare events at the threshold less than 100 eV. The construction of the gaseous detector is given and the typical pulses with amplitudes of a few eV observed on a bench scale installation are presented. The possible implications for future experiments are discussed.